2019
DOI: 10.1101/819540
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathological modeling of TBEV infection reveals differential innate immune responses in human neurons and astrocytes that correlate with their susceptibility to infection

Abstract: Tick-borne encephalitis virus (TBEV) is a member of the Flaviviridae family, Flavivirus genus, which includes several important human pathogens. It is responsible for neurological symptoms that may cause permanent disability or death, and, from a medical point of view, is the major arbovirus in Central/Northern Europe and North-eastern Asia. TBEV tropism is critical for neuropathogenesis, yet, little is known about the molecular mechanisms that govern the susceptibility of human brain cells to the virus. In th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…al. showed that at early stages of the infection human TBEV infected astrocytes show TLR3 expression that is close to basal levels, whereas at 24 hpi TLR3 expression is significantly enhanced (57). We also observed induction of TLR3 upon infection of both, WT and MAVS ko astrocytes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…al. showed that at early stages of the infection human TBEV infected astrocytes show TLR3 expression that is close to basal levels, whereas at 24 hpi TLR3 expression is significantly enhanced (57). We also observed induction of TLR3 upon infection of both, WT and MAVS ko astrocytes.…”
Section: Discussionsupporting
confidence: 68%
“…During TBEV infection of human astrocytes, the RLRs RIG-I and MDA5, but not TLR3, sense TBEV NS5 and activate IRF-3 signaling, which leads to the production of CCL5 (58). A recent study analyzing RNA expression profiles of TBEV infected human neuro-glia cultures, i.e., neuron and astrocyte cocultures, showed that in astrocytes the transcripts of Ddx58, Oas2, IFN-β, Mx1, Trim5a and Rasd2 were even more abundantly induced than in neurons (57). We also observed upregulation of these transcripts in TBEV infected WT astrocytes, whereas in MAVS ko astrocytes the induction of the respective transcripts was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…During TBEV infection of human astrocytes, the RLRs RIG‐I and MDA5, but not TLR3, sense TBEV NS5 and activate IRF‐3 signaling, which leads to the production of CCL5 (Zheng et al, 2018). A recent study analyzing RNA expression profiles of TBEV‐infected human neuro‐glia cultures, that is, neuron and astrocyte cocultures, showed that in astrocytes the transcripts of Ddx58, Oas2, IFN‐ β , Mx1, Trim5a , and Rasd2 were even more abundantly induced than in neurons (Fares et al., 2020). We also observed upregulation of these transcripts in TBEV‐infected WT astrocytes, whereas in MAVS ko astrocytes the induction of the respective transcripts was significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Fares et al showed that at early stages of the infection, human TBEV‐infected astrocytes show TLR3 expression that is close to basal levels, whereas at 24 hpi TLR3 expression is significantly enhanced (Fares et al., 2020). We also observed induction of TLR3 upon infection of both, WT and MAVS ko astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation